Characterization of Antibiotic Actinomycin D Isolated from Streptomyces parvulus Collected from Marine Sponge of Barrang Lompo Island, Makassar, Indonesia - Rante, Herlina; Alam, Gemini; Murti, Yosi Bayu; Ali, Alimuddin (Infectious Disorders - Drug Targets, 2025)
BackgroundMicroorganisms associated with sea sponges have proven to be good natural product resources that are biologically active and pharmaceutically important.ObjectiveThis research aimed to identify actinomycetes related to a sponge from Barranglompo Island Makassar and the antibacterial compounds.MethodsIdentification of actinomycetes was based on molecular characterization of sequence gen16S rRNA. The antibacterial compound was separated using vacuum liquid chromatography and preparative Thin Layer Chromatography (TLC). The structure determination was done based on spectroscopy 1H-NMR, 13C-NMR, 2D NMR, and mass spectra.ResultsMolecular characterization showed that actinomycetes strain BLP 20 had the closest relationship with Streptomyces parvulus and Uncultured Streptomyces sp. with a similarity value of 83%. The results obtained from the characterization of antibacterial compounds based on spectroscopic data indicate that these compounds lead to Actinomycin D.ConclusionCharacterization and identification of Strain 20 / BLP by molecular phylogenetic analysis of 16S rRNA sequences revealed the closest relationship with Uncultured Streptomyces sp and S. parvulus with a similarity value of 83%, which indicated a new species. The structure of the active compound isolated from actinomycetes strain 20 / BLP leads to Actinomycin D.
Keywords: antibacterial